ANALYSIS OF PHOSPHATE DEPOSIT “DISTURBANCES” USING THE HORIZONTAL-GRADIENT RESPONSES OF RESISTIVITY DATA (OULAD ABDOUN, MOROCCO) - Bakkali Saad (Earth Sciences Research Journal)
In the great Oulad Abdoun Basin exploitation of a new phosphate deposit was begun after the Grand Daoui horizon was exhausted. Inclusions of sterile hardpan-so-called "disturbances" -are hard to detect and interfere with phosphate extraction. Their resistivity is above 200 Ω.m as against 80 to 150 Ω.m for the phosphate-rich mineral. A Schlumberger resistivity survey over an area of 50 hectares was carried out. Models of the geology were successfully obtained from the analysis of the horizontal-gradient map of "disturbances". A new field procedure was tested to estimate the depth of disturbances. Phosphate reserves were better known.